Quasi-Homogeneous Black Hole Thermodynamics in Non-Commutative Geometry - Hernando Quevedo; María N. Quevedo (Universe)
We study the thermodynamic properties of a black hole that takes into account the effects of non-commutative geometry. To emphasize the role of new effects, we have chosen a specific modified Schwarzschild black hole inspired by non-commutative geometry. We show that, in order to apply the laws of quasi-homogeneous thermodynamics using the formalism of geometrothermodynamics, it is necessary to consider the non-commutative parameter as an independent thermodynamic variable. As a result, the properties of the black hole change drastically, leading to phase transitions that are directly related to the value of the non-commutative parameter. We also prove that an unstable commutative black hole can become stable in non-commutative geometry for particular values of the non-commutative parameter.